Digital Transformation in Education: Challenges and Opportunities in Improving the Quality of Learning in the Era of Revolution - Akfal, Ahmad Zaenul; Solekh, Ilham Efendi; Saefiansyah, Putra Maulana (Proceedings Series on Social Sciences & Humanities, 2025)
Digital transformation in education has become a necessity in the midst of the Industrial Revolution 4.0 and Society 5.0, which demand a rapid adaptation to technology. The application of digital technology in learning not only affects teaching methods but also opens up opportunities for a significant improvement in the quality of education. On the other hand, this process also presents various challenges such as access inequality, limited digital literacy, and resistance to change. This article aims to comprehensively examine the challenges and opportunities faced in the process of digital transformation in education. The method used is a literature study of various academic sources and the latest policies. The study's results indicate that although there are significant obstacles in terms of infrastructure and human resource readiness, digital transformation remains a strategic opportunity to achieve inclusive, adaptive, and quality education. For this, a synergy between the government, educational institutions, educators, and society is needed to create a digital ecosystem that supports 21st-century learning.